[OP.5B.08] ASSOCIATION BETWEEN CARDIOVASCULAR RISK SCORE AND RHEUMATOLOGICAL DISEASE ACTIVITY SCORE IN RHEUMATOID ARTHRITIS PATIENTS. (September 2017) - Maloberti, A.; Boggioni, I.; Di Gennaro, G.; Valena, C.; Riva, M.; Pozzi, M.; Grassi, G.
Abstract : Objective: Reumatoid Arthritis (RA) patients display an increased cardiovascular (CV) risk. It is still debated, however, which CV risk chart is more adequate to define the CV risk profile of individual RA patient. Our study was aimed at assessing the ESH/ESC score in determining the CV risk and to compare the results with those obtained via the Framingham Risk Score (FRS) and the SCORE, both as classic and as modified according to EULAR recommendations. Design and method: Anamnestic data, clinic blood pressure (BP) and laboratory data were collected in 55 consecutive RA patients. Rheumatological score of disease activity (DAS28 Erythrocyte sedimentation rate - ESR, CDAI and SDAI) and CV risk model (FRS, SCORE, ESH/ESC) were calculated with a correcting factor of 1.5 when patients displayed at least 2 out of 3 of the following conditions: a long standing diseases (>10 years), with extra-articular disease or seropositivity for Reumatoid Factor (RF) or Anti–citrullinated protein antibody (ACPA) - modified score (mFRS and mSCORE). Results: Mean (±SD) age was 62.8 ± 8.9 years, 23.6% were males and BP amounted to 130.6 ± 17.4/ 75.6 ± 8.9 mmHg. Mean DAS28 ESR, CDAI and SDAI were 3.3 ± 1.3, 8, 9 ± 9.7 and 9.7 ± 10.1 respectively, indicating a low disease activity. The majority of patients showed a low CV risk employing mFRS, mSCORE and ESH/ESC (percent values: 67.9, 94.3 and 58.4, respectively). When patients were divided according to their low, medium or high risk, the different groups didn't show any significant difference regarding DAS28ESR, CDAI, SDAI and age of RA. Only with FRS a significant difference in DAS28ESR was found with greater values in the high risk group. Moreover the only significant correlation was found between both FRS and mFRS with DAS28ESR (r = -0.3, P = 0.02). Conclusions: In RA patients only FRS risk score significantly correlates with the disease activity index both with and without EULAR correcting factor. On the contrary no significant correlation was found SCORE and ESH/ESC models, which thus appear to less sensitivitive in categoriziing Cv risk in RA patients.